2019
DOI: 10.1016/j.jcbs.2018.09.005
|View full text |Cite
|
Sign up to set email alerts
|

The Acceptance and Action Questionnaire-II (AAQ-II) as a measure of experiential avoidance: Concerns over discriminant validity

Abstract: Conflict of interest: Ian Tyndall declares that he has no conflict of interest. Daniel Waldeck declares that he has no conflict of interest. Robert Whelan declares that he has no conflict of interest. Bryan Roche declares that he has no conflict of interest. David Dawson declares that he has no conflict of interest. Luca Pancani declares that he has no conflict of interest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
126
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 215 publications
(140 citation statements)
references
References 53 publications
8
126
0
6
Order By: Relevance
“…Our findings lend support to usage of context-specific AAQs when they exist and have been empirically validated along psychometric dimensions relevant to the study design (e.g., established treatment sensitivity for a clinical trial). Furthermore, although the AAQ-II is thought to be a psychometrically solid measure of general psychological flexibility, limitations with respect to item sensitivity, measurement invariance across samples, and discriminant CONTEXT-SPECIFIC MEASURES OF PSYCHOLOGICAL FLEXIBILITY 11 validity have been noted (Ong, Pierce, Woods, Twohig, & Levin, 2018;Tyndall et al, 2018;Wolgast, 2014). The extent to which the context-specific AAQs share these limitations is unclear and further psychometric investigation is needed to fully evaluate their utility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings lend support to usage of context-specific AAQs when they exist and have been empirically validated along psychometric dimensions relevant to the study design (e.g., established treatment sensitivity for a clinical trial). Furthermore, although the AAQ-II is thought to be a psychometrically solid measure of general psychological flexibility, limitations with respect to item sensitivity, measurement invariance across samples, and discriminant CONTEXT-SPECIFIC MEASURES OF PSYCHOLOGICAL FLEXIBILITY 11 validity have been noted (Ong, Pierce, Woods, Twohig, & Levin, 2018;Tyndall et al, 2018;Wolgast, 2014). The extent to which the context-specific AAQs share these limitations is unclear and further psychometric investigation is needed to fully evaluate their utility.…”
Section: Discussionmentioning
confidence: 99%
“…Little research has been done on the discriminant validity of context-specific measures of psychological flexibility, which would provide information on their precision. The AAQ-II¾on which most measures reviewed in this article were based¾has at times been shown to correlate highly with measures of negative affect, distress, and mindfulness (Tyndall et al, 2018;Wolgast, 2014). While some association between these variables is to be expected, researchers have argued that the AAQ-II does not demonstrate strong enough discriminant validity to reliably measure psychological flexibility and that other measures should be considered (Rochefort, Baldwin, & Chmielewski, 2017).…”
Section: Future Researchmentioning
confidence: 93%
“…The AAQ-II has been found to predict a range of mental health problems (Levin et al, 2014) and mediate treatment outcomes for ACT (e.g., Pots, Trompetter, Schreurs, & Bohlmeijer, 2016;Yadavaia, Hayes, & Vilardaga, 2014). However, there are also validity concerns with the AAQ-II such as a high overlap with psychological distress (Tyndall et al, 2019;Wolgast, 2014), lack of precision with regards to measuring experiential avoidance or some/all aspects of psychological inflexibility (Gámez, Chmielewski, Kotov, Ruggero, & Watson, 2011), and notably high correlations with other ACT processes such as cognitive fusion (Gillanders et al, 2014). The AAQ-II has also been found to be less sensitive to detecting effects than domain-specific measures of psychological inflexibility (Ong, Lee, Levin, & Twohig, 2019).…”
Section: Developing Adequate Process Measuresmentioning
confidence: 99%
“…The fact that the AAQ-II consists only of negatively worded items focused on maladaptive behavioural outcome, led to the criticism regarding the lack of incremental validity compared to existing scales measuring psychological distress (Gámez et al, 2014). Some authors suggested that the instrument was actually a measure of psychological distress, well-being and functioning rather than psychological flexibility (Tyndall et al, 2019;Wolgast, 2014). Furthermore, Vaughan-Johnston, Quickert, and MacDonald (2017) stressed the absence of incremental validity of the AAQ-II in predicting reactions to situational stimuli, while controlling the variables of present affect, neuroticism, and anxious attachment.…”
mentioning
confidence: 99%
“…In most of these studies, experiential avoidance was found to be a transdiagnostic deleterious process resulting in a state of lower functionality, or as a predisposing factor placing people at risk of developing psychopathological symptoms. Although higher levels of experiential avoidance have been associated with higher risks of many forms of psychopathology (Levin et al, 2014), the potential of the AAQ-II in discriminating clinical and nonclinical samples has not been adequately demonstrated (Karekla & Michaelides, 2017;Tyndall et al, 2019). In the past decade, there has also been a noticeable trend in developing variations of the AAQ in more disorder-specific manner, in order to evaluate the role of experiential avoidance in particular conditions, including psychosis (Shawyer et al, 2007), chronic pain (Vowles, McCracken, McLeod, & Eccleston, 2008), social anxiety (MacKenzie & Kocovski, 2010), body-image (Sandoz, Wilson, Merwin, & Kellum, 2013), substance abuse (Luoma, Drake, Hayes, & Kohlenberg, 2011), smoking dependence (Gifford et al, 2002), and weight-related issues (Lillis & Hayes, 2008).…”
mentioning
confidence: 99%